2011
DOI: 10.4065/mcp.2011.0092
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Coronary Heart Disease Mortality—An Obesity or a Lean Paradox?

Abstract: Body Composition and Heart disease mortalityFor personal use. Mass reproduce only with permission from Mayo Clinic Proceedings a .D espite the well-known adverse affects of obesity on almost all aspects of coronary heart disease (CHD) and CHD risk factors, including hypertension (HTN), plasma lipids, inflammation, glucose abnormalities, insulin resistance, metabolic syndrome and type 2 diabetes mellitus (T2DM), as well as left ventricular hypertrophy (LVH), many studies of cohorts with established cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 44 publications
(51 reference statements)
5
70
1
6
Order By: Relevance
“…BMI is the most frequently used method to assess obesity and has shown many advantages as a surrogate of body fat, such as simplicity and reproducibility, and epidemiologic studies have shown an association between extreme values of BMI and increased mortality [27,28] . However, a significant limitation of using BMI is its failure to reflect true body fatness [29] and to assess the risk of obesity-related diseases in persons with low muscle and high body fat [30] , especially in individuals with increased body fat and normal BMI. WC, an essential component of metabolic syndrome diagnosis, has been used to measure total adiposity and is a good indicator of metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is the most frequently used method to assess obesity and has shown many advantages as a surrogate of body fat, such as simplicity and reproducibility, and epidemiologic studies have shown an association between extreme values of BMI and increased mortality [27,28] . However, a significant limitation of using BMI is its failure to reflect true body fatness [29] and to assess the risk of obesity-related diseases in persons with low muscle and high body fat [30] , especially in individuals with increased body fat and normal BMI. WC, an essential component of metabolic syndrome diagnosis, has been used to measure total adiposity and is a good indicator of metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…(1,(88)(89)(90) What is certain is that fitness is important to improve prognosis among CAD patients (81)(82)(83) and, therefore, physical activity, exercise training and fitness improvements, with potentially accompanying purposeful weight loss, should be incorporated into treatment plans of overweight or obese patients with CAD. (84,85) …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(36,74,75,(77)(78)(79)(80)(81)(82)(83)(84)(85)(86) Weight loss has been associated with marked improvements in arterial pressure and LV geometry, potentially improving HTN. (86) Additionally, exercise, a potential tool for weight loss, has been associated with increases in cardioprotective HDL-C, increased insulin sensitivity, and a decrease in the prevalence of MetS and DM.…”
Section: Weight Loss and Cadmentioning
confidence: 99%
“…Findings suggest that the odds of having hypertension and diabetes increase with the increasing level of age, education, socioeconomic status, and BMI. For BMI, although the individuals with low BMI (say less than 18.5) tend to have smaller odds of having such cardiovascular disease compared to those with high BMI, they may have other health hazards due to nutrition deficiency (Lavie et al, 2011). Further, males, people from rural area, people working outside have lower odds of having both hypertension and diabetes.…”
Section: Resultsmentioning
confidence: 99%